A Targeted Enrichment Strategy for Massively Parallel Sequencing of Angiosperm Plastid Genomes - Gregory W. Stull; Michael J. Moore; Venkata S. Mandala; Norman A. Douglas; Heather-Rose Kates; Xinshuai Qi; Samuel F. Brockington; Pamela S. Soltis; Douglas E. Soltis; Matthew A. Gitzendanner (Applications in Plant Sciences, 2013)
Premise of the study: We explored a targeted enrichment strategy to facilitate rapid and low-cost next-generation sequencing (NGS) of numerous complete plastid genomes from across the phylogenetic breadth of angiosperms.